Examining the Impact of Implementing Quil and Google Classroom on Writing Motivation in Algerian Secondary School EFL Classrooms: The Case of 2nd Year Students at Bennaa Said Secondary School, Ain El-Hadjel, M’sila.lBot - Charifa METARFI Messaouda HADJI (My University, 2025)
The current study investigates the impact of implementing Google Classroom and QuillBot on EFL students’ writing motivation, specifically in a secondary school context. Conducted with second-year students at Bennaa Said Secondary School, the aim of this research is to prove that these digital tools enhance learners’ drive towards writing in English. This research has a qualitative-quantitative nature that focuses on a quasi-experimental design, using a single group for both pre- and post-treatment phases. The data were collected through questionnaires based on Self-Determination Theory and writing tests’ scores. The findings revealed that the mean score of the motivation questionnaire increased from M=3.56 to M=3.9, while writing test scores improved from M=7.13 to M=12.49. This suggests that integrating such educational tools has a positive impact on learners’ attitudes during writing instruction, enhancing their engagement and interest. As a result, this research emphasizes the importance and effectiveness of integrating such technological tools to support students’ writing motivation
Keywords: Key words: Google Classroom; QuillBot; writing motivation; Self-Determination Theory; EFL students